Gamifikasi dalam Pendidikan Dasar: Strategi Inovatif untuk Meningkatkan Keterlibatan dan Kreativitas Peserta Didik - Nurjanah, Siti; Candra, Iga Ayu Intan (MANDALA WIDYA: Jurnal Ilmu Pendidikan, 2025)
Learning innovation in the twenty-first century demands new approaches capable of enhancing pupil engagement and creativity. One of the principal challenges in primary education is the low level of learning motivation and learner participation during classroom processes, which subsequently constrains the development of creativity. Gamification, as a pedagogical strategy that integrates game elements into non-game contexts, has emerged as an innovative alternative to address these challenges. This article aims to analyse the application of gamification in primary education, particularly in relation to improving pupil engagement and creativity. The study employs a literature review method encompassing empirical research, meta-analyses, and theoretical discussions. The findings indicate that gamification can increase motivation, strengthen cognitive, emotional, and behavioural engagement, and foster the development of pupils’ creativity through problem-solving and collaborative activities. However, the effectiveness of gamification is significantly influenced by its design, the selection of game elements, and teachers’ readiness to implement it. This article recommends integrating gamification within the primary school curriculum and developing comprehensive teacher training programmes to ensure the sustainability of this innovative learning practice.